Clarifying customer brand engagement boundaries: A systematic literature review approach - Bilro, R. (2022)
The purpose of this research is to provide a systematic review of customer brand engagement literature, aiming (i) to bounder a comprehensive conceptualization of this construct, (ii) to summarise its most relevant dimensions, (iii) and identify core issues for future research avenues. An extensive literature review was conducted from online academic databases (EBSCO, ABI/Inform Collection, Web of Science). A total of 30 conceptual and empirical papers rating ABS 2015 3, 4 and 4+ were leached and selected. As this study highlight, research on customer brand engagement has grown considerably over the past ten years. Also, the strategic importance of enhanced understanding of customer brand engagement is increasingly recognised, while becoming a central construct in the marketing field. Consumer brand engagement is proposed as a multi−dimensional construct which comprises cognitive, emotional, behavioural and social dimensions. Also, we can recognise that the theoretical foundations of this concept arise from relationship marketing and service dominant logic. This research provides an overview of the most relevant customer brand engagement literature, focused on quality criteria and underlining future research avenues. Thus, the present study aims to serve as a valuable tool for researchers, mapping the current state of the art of customer brand engagement research in the marketing field, and promoting this research area onwards. This research also provides firms’ useful information regarding customer brand engagement management. As companies deeply understand how to engage its customers, the more efficient they will become. As far as authors know, this is the first attempt to explore systematic review of customer brand engagement that offers a detailed understanding of the current state of the art concerning this issue, and also draws a construct comprehensive conceptualization.